Influence of Solvent on the Properties of CZTS Nanoparticles. (2016) - Kannan, A.G.; Manjulavalli, T.E.; Chandrasekaran, J.
Abstract: Quaternary Cu2 ZnSnS4 (CZTS), a P-type semiconducting material with a direct band gap of 1.4 to 1.5 eV and high absorption coefficient (10 4 cm -1 ) in the visible range has been considered as an alternative absorber layer in the fabrication of solar cells owing to its earth abundant and environmentally benign constituents. In this paper, we report the study of CZTS nanoparticles synthesized by solvothermal method using five different solvents (Water, Ethylene glycol, Diethylene glycol, Ethylene diamine, and ethanol). XRD pattern of all the prepared samples shows no secondary phases and exhibits kesterite structure with preferential orientation along (112) direction and the identification is further confirmed by Raman spectrum. The crystallite sizes of the nanoparticles were found to vary from 14 nm to 7 nm. Morphological and Chemical composition of the samples reveals controlled growth and near stoichiometry ratio for the sample prepared using EG as solvent. Optical analysis indicates broad absorption in the visible region for all samples and absorption edge of the nanoparticles prepared in EG shifts towards shorter wavelength exhibiting quantum confinement effect and the estimated optical band gap of CZTS nanoparticles were found to vary from 1.39 eV to 1.53 eV. The photo responses of the samples were studied using I-V measurements which shows significant photo current for all samples.